2015
DOI: 10.1016/j.anbehav.2014.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Age matters: pheromone profiles of larvae differentially influence foraging behaviour in the honeybee, Apis mellifera

Abstract: Keywords:brood pheromone dimorphism division of labour e-beta ocimene honeybee larval feeding pheromone pollen foraging How a colony regulates the division of labour to forage for nutritional resources while accommodating for size and demographic composition is a fundamental question in the sociobiology of social insects. In honeybees, Apis mellifera, young and old larvae produce pheromones that differ in composition. Nurses differentially regulate larval nutrition, feeding young worker larvae a surplus diet t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…Furthermore, the pheromones are separated by larval age: BEP is emitted principally by old larvae and reaches a maximum concentration during the capping stage (Trouiller, Arnold, Le Conte, & Masson, 1991). In contrast, β-ocimene has been identified from different instars with multiple functions (He et al, 2016;Ma, Mueller, & Rangel, 2016;Maisonnasse et al, 2009;Traynor, Le Conte, & Page, 2014;Traynor et al, 2015). Although we cannot exclude its existence in different developmental ages, allo-ocimene has only been found so far in 1-day old larvae, a critical age for queen development that requires a specific signal for the nurse bees to identify queen-destined larvae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the pheromones are separated by larval age: BEP is emitted principally by old larvae and reaches a maximum concentration during the capping stage (Trouiller, Arnold, Le Conte, & Masson, 1991). In contrast, β-ocimene has been identified from different instars with multiple functions (He et al, 2016;Ma, Mueller, & Rangel, 2016;Maisonnasse et al, 2009;Traynor, Le Conte, & Page, 2014;Traynor et al, 2015). Although we cannot exclude its existence in different developmental ages, allo-ocimene has only been found so far in 1-day old larvae, a critical age for queen development that requires a specific signal for the nurse bees to identify queen-destined larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Individual esters or ester subsets also have some biological activity (Slessor et al, 2005). Additionally, β-ocimene, a highly volatile component, is emitted by larvae to modulate honey bee behavioural maturation and nursing behaviour (He et al, 2016;Maisonnasse, Lenoir, Beslay, Crauser, & Le Conte, 2010;Traynor, Le Conte, & Page, 2015). These brood signals are mainly perceived by the antennae (Robertson & Wanner, 2006), the central olfactory organ of all insects, in which odourant transduction occurs within a few milliseconds from the boundary layer of the antenna to olfactory receptor neurons (Leal, 2013;Szyszka, Gerkin, Galizia, & Smith, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hygienic behavior has been studied in honey bees since at least the 1960s (15), but our knowledge of the molecular mechanism behind it is incomplete. In the present work, we investigate two candidate honey bee necromones -β-ocimene (a co-opted brood pheromone (38,39,43,44)) and oleic acid (a well-known necromone in other arthropods (4-6, 9, 35, 36)) -using in vivo, ex vivo, and in vitro techniques. We demonstrated 1) that the odors are sufficient to induce hygienic behavior in realistic behavioral assays (Figure 1C), 2) despite being a viscous compound, oleic acid can stimulate nerve depolarizations worker antennae at hive temperatures (Figure 4), and 3) oleic acid and β-ocimene have high affinities to odorant binding proteins that are upregulated in hygienic honey bees (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Traynor et al (2015) investigated the role that brood of different ages have on foraging activity, including a comparison of colonies with young larvae, broodless colonies Figure 1. Average (±SEM) number of pollen foragers returning to colonies within a 5-min interval after the addition of an ocimene pheromone treatment (triangle ) or a paraffin oil control (circle ).…”
Section: Discussionmentioning
confidence: 99%
“…Maisonnasse et al (2010) therefore hypothesized that multiple worker castes could potentially assess the concentration of EBO in a colony-possibly as an indication of the number of young brood in the hive-and adjust their behaviors accordingly. Recently, Traynor et al (2015) showed that, in colonies without brood, synthetic ocimene is able to increase total foraging by approximately 35 % and the proportion of pollen foraging by 10 %. However, the effects of varying ambient EBO levels on hive behavior have yet to be explored in colonies with brood.…”
Section: Introductionmentioning
confidence: 99%